2003
DOI: 10.1682/jrrd.2003.10.0025
|View full text |Cite
|
Sign up to set email alerts
|

Controlled breathing and dyspnea in patients with chronic obstructive pulmonary disease (COPD)

Abstract: Abstract-Controlled breathing is included in the rehabilitation program of patients with chronic obstructive pulmonary disease (COPD). This article discusses the efficacy of controlled breathing aimed at improving dyspnea. In patients with COPD, controlled breathing works to relieve dyspnea by (1) reducing dynamic hyperinflation of the rib cage and improving gas exchange, (2) increasing strength and endurance of the respiratory muscles, and (3) optimizing the pattern of thoracoabdominal motion. Evidence of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
87
1
7

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(98 citation statements)
references
References 65 publications
3
87
1
7
Order By: Relevance
“…Pulmonary rehabilitation programs have been focusing on strategies to improve alveolar ventilation such as diaphragmatic breathing that seems to be related to modifications of breathing pattern (6). Studies have reported a decrease in rib cage motion and an increase in abdominal motion during diaphragmatic breathing (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…Pulmonary rehabilitation programs have been focusing on strategies to improve alveolar ventilation such as diaphragmatic breathing that seems to be related to modifications of breathing pattern (6). Studies have reported a decrease in rib cage motion and an increase in abdominal motion during diaphragmatic breathing (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…This finding confirms that enhanced mucus clearance can be achieved in healthy subjects by PLB & FETs. In particular, most previous studies found that successful PLB markedly reduced respiratory rate and dyspnoea, improved tidal volume and increased the vital capacity and oxygen saturation of patients with emphysema 10,11,20,21) . Furthermore, healthy individuals performing volitional PLB have also previously been found to exhibit significant increases in tidal volume during resting breathing and exercise as reported by Spahija et al in 1996 22) .…”
Section: Discussionmentioning
confidence: 98%
“…Our study is original research designed to evaluate the effects of PLB combined with FETs on mucus clearance. The increased clearance achieved by PLB & FETs could have resulted from the mechanical effect of PLB [1][2][3]14,15,23,24) , stimulation of mucociliary clearance resulting from forced expiration techniques 1,[5][6][7]9) or the mechanism of two-phase Due to the mechanical effect of PLB, active expiration through the half-opened lips induces expiratory mouth pressure of about 5 cmH 2 O 10,11,15) . The positive back pressure may splint the airway open, preventing compression or premature closure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations